Analisis Strategi Partai Aceh pada Pemilukada Aceh 2012 - AFDHAL AFDHAL (Politeia: Jurnal Ilmu Politik, 2014)
Local Election is a process of manifestation the democracy in regional levels in order to select the head of the region directly by the citizens to look for a leader that they want. This is study about Analysis of Aceh Party's Strategy on Aceh Local Election 2012 (Pemilukada Aceh 2012). There are five candidates spesifically: Tgk. Ahmad Tajuddin and Ir. Suriansyah, Irwandi Yusuf and Muhyan Yunan, Prof. Darni Daud and DR. Ahmad Fauzi, Muhammad Nazar, S.Ag. and Ir. Nova Iriansyah, Dr. Zaini Abdullah and Muzakkir Manaf. Aceh Election in 2012 was won by dr. Zaini Abdullah and Muzakkir Manaf (ZIKIR). This study mainly disscusses about strategies Aceh Party in the process of winning dr. Zaini Abdullah-Muzakkir Manaf on the Local Election 2012. This sudy using institutional approach and collecting data is using interviews techniques also library research. There are three strategies used by Aceh Party in the process of winning dr. Zaini Abdullah-Muzakkir Manaf on the Local Election 2012. First, internal consolidation; Second, optimizing KPA; Third, developing the personal image of ZIKIR.Keywords: Local Election, Local Political Party, Aceh Party.